Cultural competence dimensions and outcomes: a systematic review of the literature. (26th October 2015) - Alizadeh, Somayeh; Chavan, Meena
Abstract: It has been widely suggested that cultural competence is an individual's core requirement for working effectively with culturally diverse people. However, there is no consensus regarding the definition or the components of this concept and there is a dearth of empirical proof indicating the benefits of cultural competence. Therefore, a systematic review was conducted to identify the most common cultural competence dimensions proposed in recent publications and to identify whether sufficient evidence exists regarding the efficacy of cultural competence in the healthcare context. A total of 1204 citations were identified through an electronic search of databases, of which 18 publications included cultural competence frameworks, and 13 studies contained empirical data on cultural competence outcomes. The overarching themes of the review were centred around the challenges faced by the healthcare sector in many countries due to growing cultural diversity, but lack of cultural competence, leading to predicaments that arise during intercultural interactions between patients and clinicians. This review will benefit researchers exploring cultural competence as one of the research variables impacting research outcomes.